2020
DOI: 10.1007/s11548-020-02146-7
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic signal analysis of instrument–tissue interaction for minimally invasive interventions

Abstract: Purpose Minimally invasive surgery (MIS) has become the standard for many surgical procedures as it minimizes trauma, reduces infection rates and shortens hospitalization. However, the manipulation of objects in the surgical workspace can be difficult due to the unintuitive handling of instruments and limited range of motion. Apart from the advantages of robot-assisted systems such as augmented view or improved dexterity, both robotic and MIS techniques introduce drawbacks such as limited hapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Spectrogram features are the dominant representation in deep learning for audio signal processing 38 . They have been shown to yield superior classification performances and achieve promising results in combination with convolutional neural network-based architectures for speech 42 , audio event detection 43 , and medical applications 44 . Log-mel spectrograms, a widely-used spectrogram variant, are two-dimensional matrices with time windows as columns, mel-bins (frequency) as rows, and amplitude as scalar values contained in the matrix.…”
Section: Breakthrough Detection Methodsmentioning
confidence: 99%
“…Spectrogram features are the dominant representation in deep learning for audio signal processing 38 . They have been shown to yield superior classification performances and achieve promising results in combination with convolutional neural network-based architectures for speech 42 , audio event detection 43 , and medical applications 44 . Log-mel spectrograms, a widely-used spectrogram variant, are two-dimensional matrices with time windows as columns, mel-bins (frequency) as rows, and amplitude as scalar values contained in the matrix.…”
Section: Breakthrough Detection Methodsmentioning
confidence: 99%
“…Acceleration sensing methods performed by Dai et al ( 47 , 48 ) tackled tissue classification during robotic bone drilling to make conclusions about material density. Several studies proposed to capture acoustic signals during surgical drilling and milling using free-field microphones ( 49 , 53 , 54 ), condenser microphones ( 50 ), contact microphones ( 51 ), and sound recorders ( 55 ). A more complex solution was proposed by Dai et al ( 56 ), in which the authors combined a free-field microphone with an accelerometer.…”
Section: Resultsmentioning
confidence: 99%
“…Methods found in Ostler et al ( 50 ) and Seibold et al ( 51 ) represented the state-of-the-art in machine learning, as they suggested classification by using deep learning architectures during bone drilling. Ostler et al ( 50 ) extracted log-spectrograms acquired during tissue drilling. Seibold et al ( 51 ) used mel-spectrograms of the audio signals with a ResNet18 network ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…While this proof of concept was designed to determine the best technical approach for a robotic percussion, a major next step will be the evaluation of the ventral motorized instrument regarding detection of different pathologies. Furthermore, different areas of medicine already use automatized analysis, such as deep learning approaches, for medical audio signals [2,11,17,22].…”
Section: Discussionmentioning
confidence: 99%